IMPROVEMENT OF ARABIC LANGUAGE TEACHER COMPETENCY BASED ON MULTIPLE INTELLIGENCE CLASSROOM - Janniarni Toha Safutri; Suci Ramadhanti Febriani; Danial Hilmi (Lughawiyah: Journal of Arabic Education and Linguistics, 2020)
This research aims to determine the efforts made in improving the competence of Arabic teacher through multiple intelligence-based classroom management at SD Plus Al-Kautsar Malang. It used a qualitative approach with a case study research design. The data collection included observation, interviews, and documentation, while analysis techniques relied on Miles and Hubermen’ steps as follow; data reduction, data display, and conclusion. The results showed that the efforts to increase the competency of Arabic teachers through multiple intelligence-based classroom management at SD Plus Al-Kautsar Malang, including the improvement of pedagogic and professional competences. The effort to increase pedagogic competence was giving the training to educators related to the design of a lesson plan, while the effort to increase professional competence is training in applying multiple intelligence during the learning process, such as Multiple Intelligence System (MIS) and Multiple Intelligence Research (MIR) training.Penelitian ini bertujuan untuk menganalisis upaya yang dilakukan dalam meningkatkan kompetensi guru bahasa Arab melalui manajemen kelas berbasis multiple intelligences di SD Plus Al-Kautsar Malang. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Teknik pengumpulan data meliputi observasi, wawancara, dan studi dokumentasi, sedangkan teknik analisis data menggunakan langkah-langkah analisis Miles dan Hubermen sebagai berikut; reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa upaya peningkatan kompetensi guru bahasa Arab melalui manajemen kelas berbasis kecerdasan majemuk di SD Plus Al-Kautsar Malang meliputi peningkatan kompetensi pedagogik dan profesional. Upaya peningkatan kompetensi pedagogik yaitu diberikannya pelatihan kepada guru terkait pembuatan RPP, sedangkan upaya peningkatan kompetensi profesional yaitu pelatihan penerapan multiple intelligence ketika proses pembelajaran, seperti pelatihan Multiple Intelligence System (MIS) dan Multiple Intelligence Research (MIR).